Neuroendocrine and Cardiovascular Activation During Aggressive Reactivity in Dogs - Gobbo, Elena; Zupan Šemrov, Manja (Frontiers in Veterinary Science, 2021)
Our aim was to investigate cardiovascular activation by measuring changes in facial and body surface temperature using infrared thermography, and neuroendocrine activation using salivary cortisol (CORT) and serotonin concentration (SER) in dogs exhibiting aggressive reactivity in real time. Based on two factors, owner-reported past aggressive behaviors, and detailed behavioral observations collected during a Socially Acceptable Behavior test consisting of 16 subtests and based on owner-reported past aggressive behaviors, each individual was categorized as aggressive or non-aggressive. CORT and SER showed no difference in neuroendocrine activity between dogs, but aggressive dogs with higher levels of aggression were found to have lower SER. Aggressive dogs also had an increased change in facial temperature measured during the test. Aggressive dogs also had an increase in facial temperature from pre-test values. The discovery of a correlation between tail wagging and left tail wagging with aggression level and aggression-related behaviors in aggressive dogs is further evidence of the right hemisphere specialization for aggression previously reported in the literature. This study provides the first evidence that both cardiovascular and neuroendocrine systems are activated during an active act of aggression in dogs.